Enhancing Burner Efficiency on Marine Vessels: A SWOT Analysis Approach - Tjahjono, Agus; Cahyadi, Tri; Fitrianingsih, Aryanti; Rabbani, Arsy Valentino (RSF Conference Series: Engineering and Technology, 2023)
As the main heat source on board, the Thermal oil heater has a burner that is responsible for the combustion process. The burner has an important role in the operation of the Thermal oil heater. However, several problems were found in its operation, such as decreased performance and inefficient maintenance on the burner, which caused obstruction of ship operations and had an impact on company losses. This study aims to find a performance strategy for the burner to operate optimally. Based on the burner manual book found on the ship and the theory put forward by experts, This research is a qualitative study, using the SWOT method to analyze internal and external factors. To find out the cause of the decline in burner performance and also to find out the right maintenance management to prevent degradation of the burner. This research used observation, interviews, literature reviews, and documentation for data collection. Based on the author’s observations using findings, manual books, and several related journals as data sources, he also interviewed several crew members as validators as well as for comparisons. This research concludes that by maximizing maintenance time and the accuracy of maintenance time according to the running hours in the manual book, The importance of maintenance has a significant influence on the optimization of the burner, but coordination with the maintenance team is also important.